Modules: too many to count. An investigation into the innate origins of number cognition - Cusworth, Harry (The University of Edinburgh, 2012)
Human number cognition in humans is a highly specialized thing, and many varied accounts describing the development of number concepts have been proposed. This investigation lays out 3 criteria by which to judge accounts and proceeds to apply them to the accounts of Gallistel & Gelman, Spelke and Laurence & Margolis; Finding that only Spelke's account reaches all three criteria. The investigation will then look at this account more more closely and defend it against a series challenges, in doing so we also investigate the cognitive capacities of the language faculty.
Keywords: Number; Module; Spelke; Language; Cognitive; accumulator; subtizing